Battery separator and preparation method thereof, and secondary battery

By using a ceramic coating containing viscous microspheres on the lithium-ion battery separator, the shortcomings in existing separators in terms of safety and thermal stability are solved, and the effects of high liquid absorption, ionic conductivity and thermal stability are achieved.

CN119786882APending Publication Date: 2025-04-08SINOMA LITHIUM BATTERY SEPARATOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411996591.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators have challenges in improving safety and thermal stability. Ceramic coatings have poor wetting properties on electrolytes, resulting in increased internal resistance and reduced capacity.

Method used

A ceramic coating containing multiple viscous microspheres is used to control the embedded or buried state of viscous microspheres in the ceramic coating, and their distribution in the battery separator is adjusted, liquid absorption and ionic conductivity are improved, while maintaining good thermal stability and adhesion.

Benefits of technology

The high liquid absorption rate, ionic conductivity, thermal stability and adhesion of the battery separator are achieved, and the safety and electrical circulation performance of lithium batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225054530000091
    Figure BDA0005225054530000091
Patent Text Reader

Abstract

The present invention discloses a battery separator and a preparation method thereof, and a secondary battery. The battery separator comprises a base film and a coating applied on at least one surface of the base film, wherein the coating is a ceramic coating containing a plurality of sticky microspheres, wherein the contact surface between the ceramic coating and the base film is the inner surface, and the other opposite surface is the outer surface, wherein 20 to 70% of the sticky microspheres protrude from the outer surface of the ceramic coating, and the remaining sticky microspheres are buried below the outer surface. The present invention controls the embedding or burying state of the sticky microspheres in the ceramic coating, and regulates the proportion of the embedded or buried sticky microspheres, so that the ceramic coating has a higher liquid absorption rate, a higher ionic conductivity, a smaller air permeability, a smaller thermal shrinkage (150°C), and a higher adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary battery separators, and in particular relates to a battery separator and a preparation method thereof, and a secondary battery. Background Art

[0002] Lithium-ion batteries are widely used in mobile phones, laptops, and on-board power supplies for automobiles due to their high voltage, high specific energy, long cycle life, and no pollution. Lithium-ion batteries are mainly composed of positive / negative electrode materials, electrolytes, separators, and battery shells. The separator is an important component of lithium-ion batteries, which is used to separate the positive and negative electrodes, prevent internal short circuits in the battery, and provide a channel for the movement of lithium ions as an electrolyte carrier.

[0003] The performance of the battery separator determines the interface structure, internal resistance, etc. of the battery, and directly affects the battery's rate performance, cycle performance, and safety performance (high temperature resistance) and other characteristics. A separator with excellent performance plays an important role in improving the overall performance of the battery.

[0004] As new energy vehicles place increasing demands on battery safety, higher requirements are also placed on the performance of diaphragms. Currently, the main method to improve safety is to coat the diaphragm surface with a ceramic coating. However, inorganic powders have poor wettability to electrolytes, and the channels on the coated diaphragm surface are small, which can increase the internal resistance of the battery and reduce capacity.

[0005] We propose a battery separator to solve the above problems. Summary of the invention

[0006] The object of the present invention is to provide a battery separator which has good thermal stability, high adhesion, high liquid absorption rate and high ionic conductivity while maintaining appropriate air permeability.

[0007] The present invention also aims to provide a method for preparing the above-mentioned battery separator.

[0008] Another object of the present invention is to provide a secondary battery.

[0009] In the first aspect, the present invention provides a battery separator, comprising a base film and a coating applied on at least one surface of the base film, wherein the coating is a ceramic coating containing a plurality of sticky microspheres, the contact surface between the ceramic coating and the base film being the inner surface, and the other opposite surface being the outer surface, 20 to 70% of the sticky microspheres protrude from the outer surface of the ceramic coating, and the remaining sticky microspheres are buried below the outer surface.

[0010] In a second aspect, the present invention provides a method for preparing a battery separator, comprising the following steps:

[0011] The ceramic particles are mixed with water, dispersed to form an inorganic dispersion, and then a viscous microsphere solution is added and dispersed evenly to obtain a finished slurry; the solid content of the viscous microsphere solution is 10 to 40 wt%, preferably 20 to 30 wt%; the solid content of the finished slurry is 28 to 40 wt%, preferably 28 to 38 wt%, and more preferably 28 to 33 wt%;

[0012] The finished slurry is coated on the base film by a coating machine, the depth of the gravure roll is 20 to 100 μm, preferably 20 to 60 μm, the coating speed is 50 to 250 m / min, preferably 100 to 160 m / min, and then dried in two stages to obtain the diaphragm;

[0013] The two-stage drying is as follows: the first stage drying pressure is positive pressure, the drying pressure is 10-100Pa, the drying temperature is 80-100°C, and the second stage drying pressure is negative pressure, the drying pressure is -80-0Pa, and the drying temperature is 50-70°C; or,

[0014] The two-stage drying is as follows: the first stage drying pressure is positive pressure, the drying pressure is 10-100Pa, and the drying temperature is 80-100°C; the second stage drying pressure is positive pressure, the drying pressure is 30-60Pa, and the drying temperature is 50-70°C.

[0015] In a third aspect, the present invention provides a secondary battery comprising the battery separator described above.

[0016] Beneficial effects of the present invention:

[0017] The present invention controls the embedding or embedding state of the viscous microspheres in the ceramic coating, as well as the proportion of the embedded or embedded viscous microspheres, so that the ceramic coating has higher liquid absorption rate, higher ion conductivity, smaller air permeability, smaller thermal shrinkage (150°C) and higher adhesion. When applied to lithium batteries, the ceramic coating has higher safety, better thermal stability, better electrical cycle performance and higher ion conductivity. DETAILED DESCRIPTION

[0018] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0019] The present invention provides a battery separator, comprising a base film and a coating applied on at least one surface of the base film, wherein the coating is a ceramic coating containing a plurality of sticky microspheres, wherein the contact surface between the ceramic coating and the base film is the inner surface, and the other opposite surface is the outer surface, wherein 20% to 70% of the sticky microspheres protrude from the outer surface of the ceramic coating, and the remaining sticky microspheres are buried below the outer surface, such as 20% of the sticky microspheres protrude from the outer surface and 80% are buried below the outer surface, or 30% of the sticky microspheres protrude from the outer surface and 70% are buried below the outer surface, or 40% of the sticky microspheres protrude from the outer surface and 70% are buried below the outer surface. The sticky microspheres protrude from the outer surface, and 60% are buried below the outer surface, or 50% of the sticky microspheres protrude from the outer surface, and 50% are buried below the outer surface, or 60% of the sticky microspheres protrude from the outer surface, and 40% are buried below the outer surface, or 70% of the sticky microspheres protrude from the outer surface, and 30% are buried below the outer surface. In the present invention, "quantity" refers to the number of sticky microspheres. For the sticky microspheres protruding from the outer surface, the protruding volume is not limited. For a certain sticky microsphere protruding from the outer surface of the ceramic coating, the protruding volume can account for most of the total volume of the sticky microsphere, or it can account for a small part of the total volume of the sticky microsphere.

[0020] The percentage of sticky microspheres protruding from the outer surface of the ceramic coating in the battery separator is calculated by the following method:

[0021] Ten 5 cm × 5 cm diaphragm samples were cut, of which five were cut vertically along the TD direction. The Zeiss field emission scanning electron microscope (ZEISS SIGMA 300, 500 times the field of view) was used to observe the range of the microscope. The number of sticky microspheres was recorded as n1, the number of sticky microspheres protruding from the outer surface of the ceramic coating was recorded as n2, and the proportion of sticky microspheres protruding from the outer surface of the ceramic coating in the TD direction was n. TD =n2 / n1, repeat the test for 5 groups of samples and take the average value; another 5 samples were cut vertically along the MD direction and observed using a Zeiss field emission scanning electron microscope (ZEISS SIGMA 300 under a 500x electron microscope field of view). The number of sticky microspheres within the viewing range was recorded as n3, the number of sticky microspheres protruding from the outer surface of the ceramic coating was recorded as n4, and the proportion of sticky microspheres protruding from the outer surface of the ceramic coating in the MD direction was n. MD = n4 / n3, repeat the test for 5 groups of samples and take the average value, then the proportion of microspheres protruding from the outer surface of the ceramic coating = (n TD +n MD ) / 2.

[0022] The battery separator provided by the present invention has viscous microspheres dispersed in the ceramic coating, part of the viscous microspheres protrude from the outer surface of the ceramic coating, and part of the viscous microspheres are buried in the ceramic layer. The protruding viscous microspheres leak out of the ceramic coating. After hot pressing with the electrode, the protruding viscous microspheres form channels between each other for storing electrolyte and circulating electrolyte, thereby improving the ion transmission capacity of the electrolyte and the adhesion between the separator and the electrode; the viscous microspheres buried in the ceramic coating support the ceramic coating and improve the heat resistance of the ceramic layer. The inventor found in the research and development process that by controlling 20% ​​to 70% of the viscous microspheres in the battery separator to protrude from the outer surface of the ceramic coating, the battery separator can have good air permeability, thermal stability, adhesion, ionic conductivity and liquid absorption rate. Too many or too few viscous microspheres protruding from the outer surface of the ceramic coating will lead to an imbalance in the performance of air permeability, thermal stability, adhesion, ionic conductivity and liquid absorption rate. In the battery separator of the present invention, preferably 50-60% of the adhesive microspheres protrude from the outer surface of the ceramic coating.

[0023] The battery separator described in the present invention, the ceramic particles in the ceramic coating contain one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide, and silicon carbide. Preferably, the ceramic particles in the ceramic coating are boehmite.

[0024] The battery separator of the present invention has an average particle size D v50 It can be 0.05 to 1.5 μm, such as 0.05 μm, 0.1 μm, 0.5 μm, 0.7 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.5 μm, preferably 0.1 to 1.0 μm.

[0025] In the battery separator of the present invention, the thickness of the ceramic coating is 1 to 5 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm.

[0026] The battery separator described in the present invention, the viscous microspheres include one or more of polyimide water-soluble microspheres, styrene-butadiene rubber microspheres, polyacrylate modified microspheres, polyetherimide, aramid, aromatic sulfone, polyvinylidene fluoride, polymethyl methacrylate, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene, preferably polymethyl methacrylate.

[0027] In the battery separator of the present invention, the glass transition temperature of the polymethyl methacrylate is 30 to 110° C., such as 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., preferably 40 to 100° C., and more preferably 50 to 90° C. If the glass transition temperature is too low, the liquid absorption rate and ionic conductivity will be greatly reduced. If the glass transition temperature is too high, the thermal stability, air permeability, liquid absorption rate and ionic conductivity of the battery separator will be affected.

[0028] The battery separator of the present invention is characterized in that the average particle size D of the sticky microspheres is v50 It is 1 to 10 μm, such as 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, preferably 2 to 8 μm, and more preferably 2 to 6 μm.

[0029] The battery separator of the present invention, the base film is made of polyethylene and / or polypropylene, and the thickness of the base film is 2.5-15 μm, such as 2.5 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm.

[0030] In the battery separator of the present invention, the solid mass ratio of ceramic particles to sticky microspheres in the ceramic coating is (20-40):(1-3), such as 20:3, 20:2, 20:1, 25:1, 30:1, 30:2, 35:1, 40:1, preferably (25-35):(1-2).

[0031] In the battery separator of the present invention, the ceramic coating is coated on one or both surfaces of the base film.

[0032] The present invention also provides a method for preparing the above-mentioned battery separator, which is a recommended method of the present invention, but does not mean that the battery separator of the present invention can only be prepared by this method.

[0033] The method for preparing the battery separator of the present invention comprises the following steps:

[0034] The ceramic particles are mixed with water, dispersed to form an inorganic dispersion, and then a viscous microsphere solution is added and dispersed evenly to obtain a finished slurry; the solid content of the viscous microsphere solution is 10-40wt%, such as 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, preferably 20-30wt%; the solid content of the finished slurry is 28-40wt%, such as 28wt%, 29wt%, 30wt%, 31wt%, 32wt%. t%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, the solid content of the finished slurry will directly affect the floating degree of the sticky microspheres. The higher the solid content, the smaller the floating degree, and the lower the solid content, the higher the floating degree. The present invention uses a finished slurry with a solid content of 28-40%, so that the sticky microspheres are solidified inside the coating to avoid floating and sinking. The preferred solid content is 28-38wt%, and more preferably 28-33wt%. 。

[0035] The finished slurry is coated on the base film by a coating machine, the depth of the gravure roller is 20-100 μm, such as 20 μm, 30 μm, 50 μm, 70 μm, 90 μm, 100 μm, preferably 20-60 μm, and the coating speed is 50-250 m / min, such as 50 m / min, 100 m / min, 150 m / min, 200 m / min, 250 m / min, preferably 100-160 m / min. The deeper the gravure depth, the lower the position of the viscous microspheres in the coating. The structural stability diaphragm of the present invention selects a gravure roller with a deeper depth for coating when the coating amount requirement is met, and then undergoes two-stage drying to obtain the diaphragm after the drying is completed.

[0036] In the two-stage drying, the drying pressure in the first stage is positive pressure, the drying pressure is 10-100Pa, such as 10Pa, 20Pa, 30Pa, 40Pa, 50Pa, 60Pa, 70Pa, 80Pa, 90Pa, 100Pa, and the drying temperature is 80-100°C, such as 80°C, 85°C, 90°C, 95°C, 100°C. The drying pressure in the second stage is negative pressure, the drying pressure is -80-OPa, such as -80Pa, -70Pa, -60Pa, -50Pa, -40Pa, -30Pa, -20Pa, -10Pa, 0, the drying temperature is 50-70°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, and the diaphragm is obtained after the drying is completed.

[0037] Alternatively, in the two-stage drying, the drying pressure in the first stage is positive pressure, the drying pressure is 10-100 Pa, such as 10Pa, 20Pa, 30Pa, 40Pa, 50Pa, 60Pa, 70Pa, 80Pa, 90Pa, 100Pa, and the drying temperature is 80-100°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, and the drying pressure in the second stage is also positive pressure, the drying pressure is 30-60Pa, such as 30Pa, 40Pa, 50Pa, 60Pa, and the drying temperature is 50-70°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, and the diaphragm is obtained after the drying is completed.

[0038] The total length of the two-stage oven is ≥15m, for example, it can be 15m, 16m, 17m, 18m, 19m, 20m, 21m, 22m. Preferably, the total length of the oven is 18-20m, more preferably 18m.

[0039] The length ratio of the first stage oven to the second stage oven is 1:(1-3), preferably 1:(1.2-2.5), more preferably 1:(1.5-2), and even more preferably 1:2.

[0040] The method of the present invention adopts a two-stage drying method, wherein at least the first stage of drying is carried out under positive pressure conditions, and both stages can be dried under positive pressure conditions. The pressure in the first stage of drying is controlled to be 10-100 Pa positive pressure. If the positive pressure is too large, the amount of deposition will be small, and too many sticky microspheres will float on the surface, resulting in a decrease in the liquid absorption rate and ion conductivity of the diaphragm; if the positive pressure is too small, more sticky microspheres will be buried in the base film, affecting the air permeability and thermal stability of the diaphragm. At the same time, during the drying process, the slower the drying speed, the lower the degree of floating.

[0041] The preparation method of the battery separator described in the present invention, the finished slurry contains 0.1 to 30 parts by weight of sticky microspheres, such as 0.1 parts by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, and 15 to 40 parts by weight of ceramic particles, such as 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight.

[0042] The preparation method of the battery separator described in the present invention, the finished slurry also includes one or more of a thickener, a binder, a wetting agent and a dispersant, the amount of the thickener is ≤15 parts by weight, the amount of the binder is ≤15 parts by weight, the amount of the wetting agent is ≤3 parts by weight, and the amount of the dispersant is ≤3 parts by weight; the thickener, binder, wetting agent and dispersant are all commonly used substances in the field, wherein the thickener can be one, two or more of sodium carboxymethyl cellulose, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium alginate, and polyacrylamide; the binder can be one or more of styrene-butadiene rubber, acrylate, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, and polytetrafluoroethylene; the wetting agent can be one or more of anionic surfactants, polyethylene surfactants, and polyol surfactants, for example, it can be polyether-modified siloxane; the dispersant can be one or more of polyvinyl pyrrolidone, polyacrylamide, and polyvinyl alcohol.

[0043] A secondary battery comprises the battery separator mentioned above.

[0044] The present invention is described below by means of specific examples.

[0045] Examples 1 to 9

[0046] Boehmite and polyvinyl pyrrolidone (solid content 50%) are dispersed in water, and dispersed by sand mill (rotation speed is 1000 rpm, 30 minutes) to form a dispersion liquid, polymethyl methacrylate is added, and after uniform dispersion, acrylate (solid content is 45%), carboxymethyl cellulose (solid content is 4%), and alkylphenol polyoxyethylene ether (solid content is 100%) are added in sequence, dispersed evenly, and sieved to form a finished slurry.

[0047] The finished slurry is coated on the base film by a coating machine, the depth of the gravure roller is 40 μm, the coating speed is 150 m / min, and the traction roller pulls the slurry into the oven for drying. The oven is divided into two sections, the drying pressure of the first section is positive pressure, and the drying pressure of the second section is negative pressure. The length ratio of the first section to the second section is 1:2, and the total length of the oven is 18 m.

[0048] The amount of each raw material used and the preparation process conditions in Examples 1 to 9 are shown in Table 1.

[0049] Comparative Example 1

[0050] The only difference from Example 1 is that the drying conditions after the finished slurry is coated on the base film are different.

[0051] The battery separators prepared in the examples and comparative examples were subjected to performance tests, and the test results are shown in Table 1.

[0052] The performance test method is:

[0053] Liquid absorption rate:

[0054] Cut a sample of 2.5cm*10cm, a pole piece of 2.5cm*6cm and two A4 papers of 21cm*5cm, and stack them in the order of A4 paper, diaphragm, pole piece, and A4 paper from bottom to top. The A4 paper is exposed with a spacing of ≥3cm. The sample is pressed by a hot press (Qmesys, QM940AS) for 30s, where the upper and lower clamps of the hot press are at 85℃ and the pressure is 1000kgf. The sample is weighed and recorded as W1, and soaked in 30mL electrolyte for 60min. It is taken out to ensure that there are no obvious liquid beads on the surface of the sample, and weighed and recorded as W2. The liquid absorption rate is (W2-W1) / W1. Five groups are tested in parallel and the average value is taken. Electrolyte: LiPF61moL / LEC: EMC=3:7, VC=2.0wt%.

[0055] Air permeability (S / (100cc)):

[0056] The test was conducted in accordance with the requirements of GB / T36363-2018. A 600mm×100mm membrane sample was cut and a Wangyan air permeability meter (ASAHI Co., Ltd., EG01-55-1MR) was used for a test time of 3s. The air permeability of the membrane was measured at any position with an interval of 100mm along the 600mm TD direction. The average value of the above five test points was recorded as the air permeability of the membrane.

[0057] Thermal shrinkage (%):

[0058] Test according to the requirements of GB / T36363-2018. Cut a sample of 10cm×10cm, mark the transverse TD and longitudinal MD on the sample, measure the transverse and longitudinal widths with a fully automatic image measuring projector (Kunshan Gaopin Precision Instrument Co., Ltd., GP-300C), clamp the sample between two sealed A4 papers, place the sample in a 150℃ oven for 1h, and measure the transverse and longitudinal widths with a fully automatic image measuring projector after the sample returns to room temperature. Measure 3 times and take the average value:

[0059] MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) ÷ MD length before heating × 100;

[0060] TD heat shrinkage rate (%) = (TD length before heating - TD length after heating) / TD length before heating × 100.

[0061] Bond strength (MPa.S):

[0062] Cut samples of 2.5cm*20cm size, electrodes of 2.5cm*6cm size and two A4 papers of 21cm*5cm size, and stack them together in the order of A4 paper, diaphragm, electrode, and A4 paper from bottom to top, with the upper and lower spacing of A4 paper exposed ≥≥3cm. Use a hot press (Qmesys, QM940AS) for 30s, where the temperature of the upper and lower clamps of the hot press is 85℃ and the pressure is 1000kgf; after the hot pressing, manually peel off 5mm of the sample, clamp the electrode in the lower chuck of a tensile testing machine (Jinan Sike Testing Technology Co., Ltd., TSL-1002), and clamp the diaphragm in the upper chuck of the tensile testing machine to ensure that there is no tilt. The stretching speed is 300mm / min, and the measurement is made three times to take the average value.

[0063] Ionic conductivity (mS / cm):

[0064] Tested according to the method specified in NB / T10827-2021. Cut a φ19mm sample (φ19mm represents the diameter of the circular sample is 19mm) and assemble it into a button battery with the positive and negative shells of the CR2016 button battery, where the electrolyte is LiPF6 1mol / L, EC:EMC=3:7, VC=2.0wt%. Assemble the button battery in the order of the negative shell, diaphragm, gasket (φ15.8*0.5mm, that is, the diameter of the gasket is 15.8mm and the thickness is 0.5mm), wave shrapnel, and positive shell. Use a 1mL dropper to drop 4 drops of electrolyte to fully wet the diaphragm, seal it with a sealing machine, wipe the electrolyte on the surface of the button battery with alcohol, and leave it for 3h. Turn on the electrochemical workstation (Metrohm, PGSTAT204), select "Impedance Test" for testing, where the lower frequency limit is 10000Hz, the upper frequency limit is 100000Hz, and the current is 100mA. Test the resistance of batteries composed of one, two, three, and four layers of diaphragms respectively, and test three sets of parallel data for each group of samples. Draw a curve with the number of diaphragm layers as the horizontal axis and the corresponding battery resistance value as the vertical axis. The slope of the curve with a fitting degree ≥0.99 is the resistance value R (Ω) of the diaphragm, and the ion conductivity of the diaphragm = d / (R*A)(S / cm), where d is the thickness of the diaphragm, in cm, and A is the effective area of ​​the gasket, in cm 2 .

[0065] Table 1

[0066]

[0067] It can be seen from the data of Examples 1 to 9 and Comparative Example 1 that when the percentage of the sticky microspheres protruding from the outer surface is between 20 and 70%, the obtained battery separator has good air permeability, thermal stability, adhesion and liquid absorption rate, especially when the percentage of the sticky microspheres protruding from the outer surface is between 50 and 60%, it has more outstanding adhesion and ionic conductivity. It can be seen from Example 2 that when the proportion of the sticky microspheres protruding from the outer surface is relatively large, its adhesion, ionic conductivity and liquid absorption rate are relatively poor, especially the ionic conductivity; it can be seen from Comparative Example 1 that when the percentage of the sticky microspheres protruding from the outer surface is too small, its air permeability, thermal stability, adhesion and liquid absorption rate are not ideal. At the same time, when the method of the present invention is used to prepare a diaphragm, it can be seen from the comparison between Example 2 and Example 1 that when the Tg of PMMA is less than 50°C, the proportion of sticky microspheres protruding from the outer surface of the ceramic layer in the prepared battery diaphragm is relatively large, and although it has good thermal shrinkage and adhesion, its liquid absorption rate is greatly sacrificed; through the comparison between Example 3 and Example 1, it can be seen that when the Tg of PMMA is greater than 90°C, the proportion of sticky microspheres protruding from the outer surface of the ceramic layer in the prepared battery diaphragm is relatively small, and although the thermal stability and air permeability of the diaphragm are relatively outstanding, the adhesion, liquid absorption rate and ionic conductivity are slightly poor.

[0068] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A battery separator, comprising a base film and a coating coated on at least one surface of the base film, wherein the coating is a ceramic coating containing a plurality of sticky microspheres, characterized in that: The contact surface between the ceramic coating and the base film is the inner surface, and the other opposite surface is the outer surface. 20 to 70% of the sticky microspheres protrude from the outer surface of the ceramic coating, and the remaining sticky microspheres are buried below the outer surface.

2. The battery separator according to claim 1, characterized in that: 50-60% of the number of the adhesive microspheres protrude from the outer surface of the ceramic coating.

3. The battery separator according to claim 1, characterized in that: The ceramic particles in the ceramic coating include one or more of α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide, and silicon carbide; preferably, the ceramic particles in the ceramic coating are boehmite.

4. The battery separator according to claim 3, characterized in that: The average particle size D of the ceramic particles v50 It is 0.05 to 1.5 μm, preferably 0.1 to 1.0 μm.

5. The battery separator according to claim 1, characterized in that: The thickness of the ceramic coating is 1-5 μm.

6. The battery separator according to claim 1, characterized in that: The sticky microspheres include one or more of polyimide water-soluble microspheres, styrene-butadiene rubber microspheres, polyacrylate-modified microspheres, polyetherimide, aramid, aramid fiber, polyvinylidene fluoride, polymethyl methacrylate, thermoplastic polyurethane elastomer rubber, polyethylene terephthalate, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene, preferably polymethyl methacrylate.

7. The battery separator according to claim 6, characterized in that: The glass transition temperature of the polymethyl methacrylate is 30 to 110°C, preferably 40 to 100°C, and more preferably 50 to 90°C.

8. The battery separator according to claim 1, characterized in that: The average particle size D of the sticky microspheres v50 It is 1 to 10 μm, preferably 2 to 8 μm, and more preferably 2 to 6 μm.

9. The battery separator according to claim 1, characterized in that: The base film is made of polyethylene and / or polypropylene, and has a thickness of 2.5 to 15 μm.

10. The battery separator according to claim 1, characterized in that: The solid mass ratio of ceramic particles to adhesive microspheres in the ceramic coating is (20-40):(1-3), preferably (25-35):(1-2).

11. The method for preparing a battery separator according to any one of claims 1 to 10, characterized in that: The following steps are involved: The ceramic particles are mixed with water, dispersed to form an inorganic dispersion, and then a viscous microsphere solution is added and dispersed evenly to obtain a finished slurry; the solid content of the viscous microsphere solution is 10-40wt%, preferably 20-30wt%; the solid content of the finished slurry is 28-40wt%, preferably 28-38wt%, and more preferably 28-33wt%; the finished slurry is coated on a base film by a coating machine, the gravure roller depth is 20-100μm, preferably 20-60μm, the coating speed is 50-250m / min, preferably 100-160m / min, and then two-stage drying is performed to obtain the diaphragm after the drying is completed; The two-stage drying is as follows: the first stage drying pressure is positive pressure, the drying pressure is 10-100Pa, the drying temperature is 80-100°C, and the second stage drying pressure is negative pressure, the drying pressure is -80-0Pa, and the drying temperature is 50-70°C; or, The two-stage drying is as follows: the first stage drying pressure is positive pressure, the drying pressure is 10-100Pa, and the drying temperature is 80-100°C; the second stage drying pressure is positive pressure, the drying pressure is 30-60Pa, and the drying temperature is 50-70°C.

12. The method for preparing a battery separator according to claim 11, characterized in that: The finished slurry contains 0.1 to 30 parts by weight of adhesive microspheres and 15 to 40 parts by weight of ceramic particles.

13. The method for preparing a battery separator according to claim 11, characterized in that: The finished slurry also includes one or more of a thickener, a binder, a wetting agent and a dispersant.

14. A secondary battery, characterized in that: A battery separator comprising the battery separator according to any one of claims 1 to 10 or a battery separator prepared by the method according to any one of claims 11 to 13.